The Influence of Hedonism, Group References, and Brand Image on iPhone Purchase Decisions in Lampung Province - Liswita, Sumaria; Ifanka, Hafidh Faresi; Sideh, Suhaila (Proceeding International Conference on Information Technology and Business, 2023)
iPhone is one of Apple Inc's main products which plays a significant role in meeting consumer needs for sophisticated technology and entertainment. In addition, the assumption of certain groups in society that associate iPhone products with exclusivity and hedonic life activities means that the iPhone has its own fans. This research aims to explore the factors that influence the decision to purchase an iPhone smartphone, with a focus on psychological aspects involving hedonism, the influence of reference groups, and brand image. Through a better understanding of the influence of hedonism, reference groups, and brand image on consumer behavior, this research can make a valuable contribution to the understanding of the increasingly complex and competitive smartphone market. The aims of this This to find out how much the influence of Hedonism, Group References, and Brand Image on iPhone Purchase Decisions in Lampung Province.The research method used is associative causality with purposive sampling technique. Data was collected through a questionnaire with 100 sample and was processed using PLS SEM. The results of this research show that hedonism and brand image affected the iPhone purchase decision in Lampung Province, while the reference group has no effect on the iPhone purchase decision in Lampung Province.Keywords—Hedonism, Reference Group, Brand Image, Purchase Decision.